1994
DOI: 10.1002/yea.320100208
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and analysis of the yeast flocculation geneFLO1

Abstract: The DNA sequence of the flocculation gene FLO1 of Saccharomyces cerevisiae, which is located on chromosome I (Watari et al., 1989) was determined. The sequence contains a large open reading frame (ORF) of 2586 bp and codes for a protein of 862 amino acids. However, further study (genomic Southern and polymerase chain reaction analyses) indicated that the gene we cloned was not the intact FLO1 gene but a form with an approximately 2 kb deletion in the ORF region. The intact FLO1 gene was then cloned and its nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
128
0
4

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(141 citation statements)
references
References 44 publications
9
128
0
4
Order By: Relevance
“…These data strongly suggest that the concomitant increase of CSH and the onset of flocculation, in ale brewing yeast cells, can now be explained by the expression of flocculins on yeast cells surface. This possibility is in agreement with the fact that N-and C-terminal regions of Flo1 protein are more hydrophobic than the rest of the protein (Watari et al 1994); N-terminal region corresponds to the domain A of Flo proteins, which is responsible by the recognition and adhesion to receptors (Kobayashi et al 1998;Veelders et al 2010). …”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These data strongly suggest that the concomitant increase of CSH and the onset of flocculation, in ale brewing yeast cells, can now be explained by the expression of flocculins on yeast cells surface. This possibility is in agreement with the fact that N-and C-terminal regions of Flo1 protein are more hydrophobic than the rest of the protein (Watari et al 1994); N-terminal region corresponds to the domain A of Flo proteins, which is responsible by the recognition and adhesion to receptors (Kobayashi et al 1998;Veelders et al 2010). …”
Section: Discussionsupporting
confidence: 65%
“…The Cdomain carries a glycosylphosphatidylinositol anchoring site to covalently bind the Flo1p to β-glucans (de Groot et al 2003). The middle part of Flo1p (domain B) contains many repeated sequences and a large number of serine and threonine residues, which O-glycosylation enables the Flo1 protein to adopt an extended conformation (Watari et al 1994). The N-terminal region of Flo1 protein (domain A) contains the sugar recognition domain, which is important for flocculation definition of Flo1 and NewFlo phenotypes (Kobayashi et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…9,[12][13][14] The five FLO genes, FLO1, FLO5, FLO9, FLO10, and FLO11, have been described in S. cerevisiae thus far. [15][16][17][18][19] The FLO1, 5, 9, and 10 genes confer cell-cell adhesion (flocculation) ability, whereas FLO11 is responsible for substrate adhesion. 20) FLO1, FLO5, and FLO9 are highly similar to each other, but FLO10 has lower similarity.…”
mentioning
confidence: 99%
“…It was reported by Straver et al (1994) that two flocculation phenotypes were distinguished by sugar inhibition, and further, they suggested the existence of at least two distinct lectin-encoding flocculation genes. To date, many genetic studies on flocculation in S. cerevisiae have reported several chromosomal genes affecting flocculation (for reviews, see Stratford, 1992;Watari et al,1994b).…”
mentioning
confidence: 99%
“…FLO1, which is one of the dominant flocculation genes, has been cloned and sequenced by three groups (Bidard et al, 1995;Teunissen et al, 1993;Watari et al, 1994b). Recently it was shown that FLO1 should be a structural gene coding for a cell surface protein, which has a key role in the mechanism of yeast flocculation, because of the localization of its product (Bidard et al, 1995), the similarity of the N-terminal sequence between the putative FLO1 product and a protein that was purified from flocculent yeast cell surface, and the stimulative effect on the flocculation ability of the yeast cells (Straver, 1994 Bunkyo-ku, Tokyo 113-8657, Japan (Received July 17, 1998; Accepted October 8, 1998) A nonflocculent industrial polyploid yeast strain, Saccharomyces cerevisiae 396-9-6V, was converted to a flocculent one by introducing a functional FLO1 gene at the URA3 locus.…”
mentioning
confidence: 99%